Naohidemyces vaccinii sporulates on wild species of ground flora in Finnish Norway spruce seed orchards but Thekopsora areolata does not on other species than Prunus - Kaitera, Juha; Aarnio, Leena; Ylioja, Tiina; Karhu, Jouni
Thekopsora areolata (Fr.) Magnus is a serious cone pathogen that reduces seed crop of Picea abies (L.) Karst. and other Picea spp. Natural sporulation of T. areolata was investigated in nine Norway spruce seed orchards suffering from severe successive T. areolata epidemics in Finland. Habitats occupied by Vaccinium myrtillus L., V. vitis-idaea L., Empetrum nigrum L. and Calluna vulgaris (L.) Hull, and a number of other wild species belonging to ground flora were investigated for Thekopsora areolata uredinia 9–10 times in May–September 2018–2019. Occurrence of Thekopsora uredinia was estimated in current-year leaves of the plants in ca. 25 sample plots of 1 m2 in each seed orchard. A sample of plant leaves with rust uredinia or necrotic pustules were collected from each plot. No rust fruiting stages of T. areolata were found on any of the test species of ground flora. However, rust uredinia were observed regularly on leaves of V. myrtillus and V. vitis-idaea in all seed orchards between mid-July and the end of September. Rust sporulation started on V. myrtillus in July and on V. vitis-idaea in August. Based on symptoms, uredinia and spore morphology, the rust on both V. myrtillus and V. vitis-idaea was identified as blueberry rust, Naohidemyces vaccinii (Jørst.) S. Sato, Katsuya & Y. Hirats. ex Vanderwegen & Fraiture. The uredinial stage of the rust on Vaccinium spp. were described. No evidence of natural sporulation of T. areolata on wild plant species other than Prunus was observed in Finnish Norway spruce seed orchards. 2021